2016
DOI: 10.1155/2016/5484568
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness and Open-Angle Glaucoma: A Meta-Analysis

Abstract: Purpose. To investigate the potential relationship between open-angle glaucoma (OAG) and peripapillary choroidal thickness (PPCT). Materials and Methods. Relevant publications were searched systematically through various databases from inception to January 2016. Studies comparing PPCT in OAG patients and healthy controls were retrieved. All qualified articles were analyzed using Stata 14.0 and Revman 5.3 software. Results. A total of 13 studies were identified for inclusion. There was a significant reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…On the other hand, in relation to studies where they used SS-OCT, a recent meta-analysis conducted by Lin et al [32] demonstrated average PPCT in open-angle glaucoma patients was significantly reduced compared with healthy subjects, especially in the superior and nasal sectors, in agreement with our results. They included different studies performed with various OCT instruments (SD and SS-OCT).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in relation to studies where they used SS-OCT, a recent meta-analysis conducted by Lin et al [32] demonstrated average PPCT in open-angle glaucoma patients was significantly reduced compared with healthy subjects, especially in the superior and nasal sectors, in agreement with our results. They included different studies performed with various OCT instruments (SD and SS-OCT).…”
Section: Discussionsupporting
confidence: 92%
“…Although it may also be the case that the choroid is thicker in Korean eyes, Chung et al33 measured PCT using Spectralis circle scans in 87 healthy Korean eyes and reported an average thickness of 157.3 μm, which is within the confidence intervals of our measurements at 900 and 1000 μm (roughly the position of a standard circle scan within our data). Several other studies have reported global PCT within standard 12° (or 3.4 mm diameter) circle scans in a wide variety of healthy participants that varies from 130 μm to 167 μm,3442 which are again within the confidence intervals of our measurements at the PCT-900 μm and PCT-1000 μm measurement points.…”
Section: Discussionsupporting
confidence: 87%
“…Hirooka et al [ 33 ] found similar results when comparing 52 NTG with 50 age-matched normal eyes. Most studies supported that PPCT was decreased in open-angle glaucoma [ 11 ], suggesting that it might be an adjunct parameter for glaucoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The innovation of enhanced depth imaging (EDI) mode has promoted an increase in the amount of researches conducted on choroidal thickness. Our previous meta-analysis [ 11 ] indicated that peripapillary choroidal thickness (PPCT) measured by OCT was significantly reduced in glaucomatous eyes compared with the normal population, suggesting that OCT-derived choroidal thickness may be an additional diagnostic marker in glaucoma patients. However, the diagnostic ability of choroidal thickness measured by SD-OCT to discriminate glaucoma from healthy subjects has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%